The ventilatory anaerobic threshold is related to, but is lower than, the critical power, but does not explain exercise tolerance at this workrate - Okudan, N.; Gökbel, H. (The Journal of Sports Medicine and Physical Fitness, 2006)
Aim: The aim of the present study was to investigate the relationships between critical power (CP), maximal aerobic power and the anaerobic threshold and whether exercise time to exhaustion and work at the CP can be used as an index in the determination of endurance. Methods: An incremental maximal cycle exercise test was performed on 30 untrained males aged 18-22 years. Lactate analysis was carried out on capillary blood samples at every 2 minutes. From gas exchange parameters and heart rate and lactate values, ventilatory anaerobic thresholds, heart rate deflection point and the onset of blood lactate accumulation were calculated. CP was determined with linear work-time method using 3 loads. The subjects exercised until they could no longer maintain a cadence above 24 rpm at their CP and exercise time to exhaustion was determined. Results: CP was lower than the power output corresponding to V.O2max, higher than the power outputs corresponding to anaerobic threshold. CP was correlated with V.O2max and anaerobic threshold. Exercise time to exhaustion and work at CP were not correlated with V.O2max and anaerobic threshold. Conclusion: Because of the correlations of the CP with V.O2max and anaerobic threshold and no correlation of exercise time to exhaustion and work at the CP with these parameters, we conclude that exercise time to exhaustion and work at the CP cannot be used as an index in the determination of endurance.